1991
DOI: 10.1254/jjp.56.167
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Saikosaponin-d on Yeast Phagocytosis and Degradation in Peritoneal Macrophages: Related Increase in Fc Receptor Expression and Altered Cytoplasmic Organization.

Abstract: ABSTRACT-The effects of saikosaponin-d (ssd), isolated from Bupleurum radix, on phagocytic functions of mouse peritoneal macrophages were investigated in macro phage cultures after treatment in vivo. We also compared the ultrastructural appear ances of macrophages from ssd-treated mice with those from control mice. The macro phages from ssd-treated mice showed a significant increase in phagocytosis, intracellu lar killing of yeast and acid phosphatase activity. Treatment of mice with ssd also in duced the Fc r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

1995
1995
2013
2013

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 25 publications
0
3
0
Order By: Relevance
“…The anti-inflammatory properties of saikosaponins have been revealed by their inhibition of mouse ear and paw edema induced by phorbol 12-myristate 13-acetate (PMA) in vivo, reduction of cyclooxygenase (COX) and lipoxygenase (LOX) production in vitro [8,9].The immunoregulatory functions of saikosaponins also include the elevation of plasma adrenocorticotropin (ACTH) and corticosterone levels in vivo [10], enhancement of antibacterial plaque-forming cell responses [11], activation of phagocytosis of macrophages [12,13], and inhibition of platelet activation and endothelial cell injury [14]. In fact, apart from the immunoregulatory functions of Saikosaponins, the cytotoxic potential of saikosaponins is also reported in the literature and hence they have been investigated as potential anti-cancer agents [15][16][17][18].…”
Section: Saikosaponins and Their Immunoregulatory Functionsmentioning
confidence: 99%
“…The anti-inflammatory properties of saikosaponins have been revealed by their inhibition of mouse ear and paw edema induced by phorbol 12-myristate 13-acetate (PMA) in vivo, reduction of cyclooxygenase (COX) and lipoxygenase (LOX) production in vitro [8,9].The immunoregulatory functions of saikosaponins also include the elevation of plasma adrenocorticotropin (ACTH) and corticosterone levels in vivo [10], enhancement of antibacterial plaque-forming cell responses [11], activation of phagocytosis of macrophages [12,13], and inhibition of platelet activation and endothelial cell injury [14]. In fact, apart from the immunoregulatory functions of Saikosaponins, the cytotoxic potential of saikosaponins is also reported in the literature and hence they have been investigated as potential anti-cancer agents [15][16][17][18].…”
Section: Saikosaponins and Their Immunoregulatory Functionsmentioning
confidence: 99%
“…Ssd can also elevate corticotropin-releasing factor mRNA level in the hypothalamus [15]. Moreover, it can activate the phagocytosis of macrophages [16], modulate T lymphocyte function [17], and upregulate IL-2/IL-4 production in thymocytes [18]. Furthermore, it has been reported that Ssd can prevent urinary protein excretion in rat models of aminonucleoside nephrosis [19], and anti-GBM nephritis [20].…”
Section: Introductionmentioning
confidence: 99%
“…It has been reported that SSd modulates T lymphocyte function (1), activates macrophage functions (2)(3)(4)(5), prevents the development of proteinuria (6), and enhances nonspecific resistance against P. aeruginosa infection (7). It has been also knownthat SSa induces cell death of a human hepatoma cell line (8) and possesses anti-inflammatory properties (9).…”
mentioning
confidence: 99%